1998
DOI: 10.2225/vol1-issue1-fulltext-4
|View full text |Cite
|
Sign up to set email alerts
|

RNA editing in plant mitochondria, cytoplasmic male sterility and plant breeding

Abstract: RNA editing in plant mitochondria is a post-transcriptional process involving the partial change of C residues into U. These C to U changes lead to the synthesis of proteins with an amino acid sequence different to that predicted from the gene. Proteins produced from edited mRNAs are more similar to those from organisms where this process is absent. This biochemical process involves cytidine deamination. The cytoplasmic male sterility (CMS) phenotype generated by the incompatibility between the nuclear and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…The function of the induced antisense transcripts in M. grisea-infected plants is not known yet. Previous studies have shown that the sense and antisense transcripts might pair in the cells to form dsRNA molecules, which may be the target for RNA editing, splicing, polyadenylation, transport, translation, and small interfering RNA (siRNA)-based gene silencing (Araya et al, 1998;Kumar and Carmichael, 1998;Hayashizaki and Kanamori, 2004;Levanon et al, 2004;Jen et al, 2005). dsRNA could be recognized as substrate by RNA-editing enzymes like adenine and cytidine deaminases (Polson et al, 1991;Smith and Sowden, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The function of the induced antisense transcripts in M. grisea-infected plants is not known yet. Previous studies have shown that the sense and antisense transcripts might pair in the cells to form dsRNA molecules, which may be the target for RNA editing, splicing, polyadenylation, transport, translation, and small interfering RNA (siRNA)-based gene silencing (Araya et al, 1998;Kumar and Carmichael, 1998;Hayashizaki and Kanamori, 2004;Levanon et al, 2004;Jen et al, 2005). dsRNA could be recognized as substrate by RNA-editing enzymes like adenine and cytidine deaminases (Polson et al, 1991;Smith and Sowden, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial genetic defect might cause premature cellular degradation of the tapetum and suppress viable pollen grain development. In all other cases where a specific CMS-associated gene has been identified, the mutation has been identified in the mitochondrial genome (Araya et al 1998, Kapoor et al 2002. The potential link between the mitochondrial genome mutation and sterility in CMS pepper should be investigated further through mitochondria genome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Araya et al . () proposed that cytoplasmic male sterility affects primarily the pollen‐producing organs because of the high energy requirement by this tissue. In Arabidopsis thaliana , mutation in editing of the atp1 ‐1178 site impairs the assembly of ATP synthase in mitochondria and results in small plants with delayed growth and development (Hammani et al ., ).…”
Section: Introductionmentioning
confidence: 99%